Mature and immature platelets during the first week after birth and incidence of patent ductus arteriosus. (28th June 2020) - Sallmon, Hannes; Metze, Boris; Koehne, Petra; Opgen-Rhein, Bernd; Weiss, Katja; Will, Joachim C.; Franke, Christina Victoria; Hansmann, Georg; Koestenberger, Martin; Bührer, Christoph; Berger, Felix; Weber, Sven C.; et al.
Abstract: Background: Thrombocytopenia is a risk factor for patent ductus arteriosus. Immature and mature platelets exhibit distinct haemostatic properties; however, whether platelet maturity plays a role in postnatal, ductus arteriosus closure is unknown. Methods: In this observational study, counts of immature and mature platelets (=total platelet count − immature platelet count) were assessed on days 1, 3, and 7 of life in very low birth weight infants (<1500 g birth weight). We performed echocardiographic screening for haemodynamically significant patent ductus arteriosus on day 7. Results: Counts of mature platelets did not differ on day 1 in infants with (n = 24) and without (n = 45) haemodynamically significant patent ductus arteriosus, while infants with significant patent ductus arteriosus exhibited lower counts of mature platelet on postnatal days 3 and 7. Relative counts of immature platelets (fraction, in %) were higher in infants with patent ductus arteriosus on day 7 but not on days 1 and 3. Receiver operating characteristic curve analysis unraveled associations between both lower mature platelet counts and higher immature platelet fraction (percentage) values on days 3 and 7, with haemodynamically significant ductus arteriosus. Logistic regression analysis revealed that mature platelet counts, but not immature platelet fraction values, were independent predictors of haemodynamically significant patent ductus arteriosus. Conclusion: During the first week of postnatal life, lower counts of mature platelets and higher immature platelet fraction values are associated with haemodynamically significant patent ductus arteriosus. Lower counts of mature platelet were found to be independent predictors of haemodynamically significant patent ductus arteriosus.